Green ergonomics and green economics: the effect of feed-in tariff schemes on user behaviours and attitudes towards energy consumption. (1st January 2012) - Morris, Robin Winslow; Stedmon, Alex W.; Langley, Alyson
On 1 April 2010 the UK government introduced 'feed-in tariff' (FIT) legislation to provide incentives for small-scale renewable energy generation, particularly by residential home-owners. This paper investigates the existing knowledge base to consider if living in a property with on-site renewable energy generation may affect user attitudes and behaviours. This knowledge is interpreted from an ergonomics/human factors perspective whilst also addressing underlying economic issues. Suggestions are made as to what effects FIT schemes may have on public attitudes and where further research efforts should be focused. A key finding is that FIT schemes are likely to result in a shift in public behaviour, particularly towards reduced energy consumption but only if initiatives address fundamental issues of green ergonomics and green economics.